2007
DOI: 10.1128/jcm.00699-07
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Candida glabrata Strain Relatedness by Pulsed-Field Gel Electrophoresis and Multilocus Sequence Typing

Abstract: In this study, 80 Candida glabrata isolates from intensive care unit and human immunodeficiency virus (HIV)-infected patients were typed by multilocus sequence typing (MLST), pulsed-field gel electrophoresis (PFGE), and mating type class determination. Among the 25 patients with multiple isolates, 19 patients (76%) contained multiple isolates exhibiting identical or highly related PFGE and MLST genotypes, which may indicate the maintenance or microvariation of one C. glabrata strain in each patient. However, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
51
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 41 publications
1
51
0
1
Order By: Relevance
“…Another finding of our study is that no microsatellite genotypes were associated with any of the clinical data recorded, as previously reported (8,12,19). Additionally, in the eight infected patients, we have shown that C. glabrata candidemia originated from colonizing isolates, as previously described for both C. glabrata (12) and C. albicans (4,22).…”
supporting
confidence: 62%
“…Another finding of our study is that no microsatellite genotypes were associated with any of the clinical data recorded, as previously reported (8,12,19). Additionally, in the eight infected patients, we have shown that C. glabrata candidemia originated from colonizing isolates, as previously described for both C. glabrata (12) and C. albicans (4,22).…”
supporting
confidence: 62%
“…Interestingly, CC64, which was not associated with a given MLST clade, corresponds in a recent paper by Lott et al (33) to an MLST group clustering as many as 18.3% of the tested strains, supported by a 99% bootstrap value (100% in the Dodgson study), each with a synapomorphic NMT1 allele (NMT1-5). Conversely, we considered genotype RT60 to be included in a potential CC since the single strain we had exhibited allele 12 for the NMT1 locus (data not shown), characteristic of clade VII (15,31,33).…”
Section: Resultsmentioning
confidence: 99%
“…Fragments of the C. tropicalis genes ICL1, MDR1, SAPT2, SAPT4, XYR1, and ZWF1a have already been analyzed (32,33). Previous reports have indicated that MLST can provide additional information on the mechanisms of genetic variability, such as the persistence, replacement, and microevolution of strains in the hosts (30,34,35).…”
mentioning
confidence: 99%